The right way to win making business ethics work in the real world - Zafft, Robert (Rowman & Littlefield, 2020)
In this pragmatic and accessible business ethics guide, students, entrepreneurs, and professionals learn that business ethics is about so much more than right and wrong. Harvard-educated and McKinsey & Co.-trained business leader Robert Zafft shows that being ethical is not an obstacle to but an essential building block for success.